2020
DOI: 10.1002/stem.3134
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing beta cell function through mesenchymal stromal cell-mediated mitochondria transfer

Abstract: Pretransplant islet culture is associated with the loss of islet cell mass and insulin secretory function. Insulin secretion from islet β‐cells is primarily controlled by mitochondrial ATP generation in response to elevations in extracellular glucose. Coculture of islets with mesenchymal stromal cells (MSCs) improves islet insulin secretory function in vitro, which correlates with superior islet graft function in vivo. This study aimed to determine whether the improved islet function is associated with mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 47 publications
(169 reference statements)
2
36
0
Order By: Relevance
“…So far, the most reported is the protective effect on stressed cells, which usually involves the mitochondria, an important organelle associated with apoptosis. Mitochondria were delivered from mesenchymal stem cells (MSCs) to injured cells in acute lung injury, allergic airway inflammation, blood vessels experiencing chemotherapy stress, or dysfunctional pancreatic islet [ 17 , 18 , 93 , 94 ]. Injured cells could also be rescued by obtaining mitochondria from neighboring healthy cells via TNTs [ 19 ].…”
Section: Versatile Functions Of Tntsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the most reported is the protective effect on stressed cells, which usually involves the mitochondria, an important organelle associated with apoptosis. Mitochondria were delivered from mesenchymal stem cells (MSCs) to injured cells in acute lung injury, allergic airway inflammation, blood vessels experiencing chemotherapy stress, or dysfunctional pancreatic islet [ 17 , 18 , 93 , 94 ]. Injured cells could also be rescued by obtaining mitochondria from neighboring healthy cells via TNTs [ 19 ].…”
Section: Versatile Functions Of Tntsmentioning
confidence: 99%
“…The ability of cells to exploit TNTs as a bridge to help other cells in pathological conditions might be a natural mechanism for tissue self-repairing. When mesenchymal stem cells were introduced into damaged cultures or tissues, the transfer of the mitochondria from these stem cells was shown to save the recipient cells by recovering their cellular metabolism [ 17 , 94 ], rescuing aerobic respiration [ 61 ], or establishing angiogenic capacity [ 93 ]. Alternatively, TNT-like structures could remove damaged organelles or autophagosomes to rescue cystinosin-deficient fibroblasts or prematurely senescent endothelial cells [ 95 , 129 ].…”
Section: Tnts As Potential Therapeutic Targetsmentioning
confidence: 99%
“…If the reduced insulin secretion in patients with T2DM is due to impaired mitochondrial bioenergetics, it would be promising to reanimate or even replace the pathologically exhaustive mitochondria. Very recently, Rackham et al [ 70 ] reported for the first time that insulin secretion can be restored by mitochondria transfer into insulin-secreting beta cells of diabetic mouse and human islets. The mitochondria were transferred by mesenchymal stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments, it has been observed that the mesenchymal stromal cells-derived mitochondria have reached approx. 30% of beta cells, which was sufficient to reinduce a functional phenotype in the intact islets [ 70 ]. This might indicate a new epoch in clinical treatments of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from the laboratory of Chloe L. Rackham (King's College London, UK) demonstrated the improved curative capacity of grafted islets in diabetic mice following co-culture with MSCs, 12,13 and further extended these encouraging findings to clinically relevant human islets and MSCs. 14,15 In their new STEM CELLS article, 8 Overall, the fascinating study highlights co-culture and cytoplasmic exchange between cells as a potentially exciting means to enhance the benefits of MSC therapy in the damaged brain.…”
Section: Msc-mediated Mitochondrial Transfer To Compromised Islet β-Cmentioning
confidence: 99%